On-line estimation of rotor-time constant of an induction motor using Recurrent Neural Networks - Mayaleh, S; Bayindir, NS (IEEE, 1998)
In this paper an on-line estimation of the rotor-time constant of induction motor using Recurrent Neural Networks is presented. Simulation results show that the neu approach is capable of fast and accurate online estimation of the rotor-time constant.
6th IEEE Power-Electronics-Society Workshop on Computers in Power Electronics (COMPEL 98) -- JUL 19-22, 1998 -- CERNOBBIO, ITALY
Keywords: Parameter-Estimation